Wnt Signaling Upregulates Teneurin-3 Expression via Canonical and Non-canonical Wnt Pathway Crosstalk - Bastías-Candia, Sussy; Martínez, Milka; Zolezzi, Juan M.; Inestrosa, Nibaldo C. (Frontiers in Neuroscience, 2019)
Teneurins (Tens) are a highly conserved family of proteins necessary for cell-cell adhesion. Tens can be cleaved, and some of their proteolytic products, such as the teneurin c-terminal associated-peptide (TCAP) and the intracellular domain (ICD), have been demonstrated to be biologically active. Although Tens are considered critical for central nervous system development, they have also been demonstrated to play important roles in adult tissues, suggesting a potential link between their deregulation and various pathological processes, including neurodegeneration and cancer. However, knowledge regarding how Ten expression is modulated is almost absent. Relevantly, the functions of Tens resemble several of the effects of canonical and noncanonical Wnt pathway activation, including the effects of the Wnt pathways on neuronal development and function as well as their pivotal roles during carcinogenesis. Accordingly, in this initial study, we decided to evaluate whether Wnt signalling can modulate the expression of Tens. Remarkably, in the present work, we used a specific inhibitor of porcupine, the key enzyme for Wnt ligand secretion, to not only demonstrate the involvement of Wnt signalling in regulating Ten-3 expression for the first time but also reveal that Wnt3a, a canonical Wnt ligand, increases the expression of Ten-3 through a mechanism dependent on the secretion and activity of the noncanonical ligand Wnt5a. Although our work raises several new questions, our findings seem to demonstrate the upregulation of Ten-3 by Wnt signalling and also suggest that Ten-3 modulation is possible because of crosstalk between the canonical and noncanonical Wnt pathways.